The Effects of Turnip Mosaic Virus Infections on the Deposition of Secondary Cell Walls and Developmental Defects in Arabidopsis Plants Are Virus-Strain Specific - López-González, Silvia; Gómez-Mena, Concepción; Sánchez, Flora; Schuetz, Mathias; Samuels, A. Lacey; Ponz, Fernando (Frontiers in Plant Science, 2021)
Two isolates of Turnip mosaic virus (UK 1 and JPN 1), representative of two different viral strains, induced differential alterations on secondary cell wall development in Arabidopsis thaliana, suggesting cell-type specific effects of these viral infections. These potential effects were analyzed in inflorescence stems and flowers of infected plants, together with other possible cellular effects of the infections. Results obtained from macroscopic and histochemical analyses showed that infection with either virus significantly narrowed stem area, but defects in secondary cell wall were only found in JPN 1 infections. In flowers, reduced endothecium lignification was also found for JPN 1, while UK 1 infections induced severe floral cell and organ development alterations. A transcriptomic analysis focused on genes controlling and regulating secondary cell wall formation also showed notable differences between both viral isolates. UK 1 infections induced a general transcriptional decrease of most regulatory genes, whereas a more complex pattern of alterations was found in JPN 1 infections. The role of the previously identified viral determinant of most developmental alterations, the P3 protein, was also studied through the use of viral chimeras. No SCW alterations or creeping habit growth were found in infections by the chimeras, indicating that if the P3 viral protein is involved in the determination of these symptoms, it is not the only determinant. Finally, considerations as to the possibility of a taxonomical reappraisal of these TuMV viral strains are provided.